Advanced Love wave sensor based on algal polymers for the detection of mercury in French Guiana waters - Wejdene Gongi; Karine Mougin; Maxence Rube; Corinne Dejous; Hatem Ben Ouada; Ollivier Tamarin (Scientific Reports)
Abstract The findings presented in this paper demonstrate the effectiveness of a new method for analyzing the electroacoustic response of Love wave acoustic sensors to assess the mechanical and dielectric properties of liquid samples. The Love wave sensor was modified by applying a solution of extracellular polymeric substances (EPS) using a self-assembled monolayer technique. The mechanical parameters of the EPS-modified sensors, such as insertion losses and phase, were found to be slightly affected by turbidity, even at high levels, while allowing a chemical detection by mass loading effect. On the other hand, the sensor electrical parameters such as capacitance and resistance showed a positive correlation with increasing turbidity. The experimental chemical detection also showed changes in the mechanical parameters (wave amplitude and phase) of the EPS-modified sensor in response to different concentrations of mercury (Hg2+), ranging from 10E−10 M to 10E−2 M. Furthermore, the study utilized response surface methodology to analyze the nonlinear behavior of the sensor under combined factors of turbidity and mercury concentration. Through this approach, a mathematical model was developed to simulate measurements of capacitance and resistance, considering both turbidity and mercury concentration as variables. This study demonstrated that integrating an EPS-Love wave sensor enables the simultaneous detection of mercury concentration and assessment of water turbidity via changes in capacitance and resistance, underscoring the sensor’s promise for high-performance environmental monitoring.